1996
DOI: 10.1111/j.1536-7150.1996.tb03203.x
|View full text |Cite
|
Sign up to set email alerts
|

From the Arena Into the Streets: Hockey Violence, Economic Incentives and Public Policy

Abstract: . The hypothesis that there is a positive relationship between violence and game attendance in the National Hockey League is tested; and the implications of the results for policies aimed at rectifying the violence considered. The empirical analysis, which is based principally on game by game data for the 1989/90 season, confirms the positive relationship, although it occurs mainly in American, not Canadian, cities. Since there is an incentive for teams to promote violence and because the legal system normall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 8 publications
2
30
2
Order By: Relevance
“…Also, fighting does not appear to attract more fans in this league. This is in contrast with studies of the NHL, which have shown positive attendance effects due to fighting in hockey games (Jones 1984;Jones et al 1993;Jones et al 1996 andPaul 2003). Fans of junior hockey may not have the same preferences for fighting in hockey games as fans of the NHL, possibly due to the players in the junior league being teenagers, rather than adults.…”
Section: Regression Model For 2009 To 2010 Qmjhl Attendancecontrasting
confidence: 61%
See 1 more Smart Citation
“…Also, fighting does not appear to attract more fans in this league. This is in contrast with studies of the NHL, which have shown positive attendance effects due to fighting in hockey games (Jones 1984;Jones et al 1993;Jones et al 1996 andPaul 2003). Fans of junior hockey may not have the same preferences for fighting in hockey games as fans of the NHL, possibly due to the players in the junior league being teenagers, rather than adults.…”
Section: Regression Model For 2009 To 2010 Qmjhl Attendancecontrasting
confidence: 61%
“…Attendance studies of hockey have mostly focused on the effects of fighting and rule changes. These studies of hockey include Jones (1984), Jones et al (1993), Jones et al (1996) and Paul (2003) in relation to the highest professional level of hockey, the National Hockey League (NHL). Recently, more general studies of hockey attendance have begun to surface including studies by Hong (2009) and Rascher et al (2009).…”
mentioning
confidence: 98%
“…This model is a recursive structural form in which attendance is dependent on price and price is determined by Equation (2). A complete structural form of this model can be seen in Jones and Ferguson (1988) and an empirical form on which this study is based can be seen in Jones, Stewart, and Sunderman (1996). The exogenous variables consist of a dummy for weekend games, dummies for early in the season (OCT for October) and late in the season (LATE, which is defined as games in March and April), dummies for the division or conference alignment of the opponent, variables on home and visiting team success, scoring, and violence, and location-specific variables such as income, population, and existence of other professional sports teams.…”
Section: Variations In Nhl Attendancementioning
confidence: 99%
“…While Siegfried and Hinshaw (1979) and Zlatoper (1994, 1999) estimate attendance functions for U.S. professional football, Price and Sen (2003) estimate game-day attendance functions for U.S. college football. Jones, Stewart and Sunderman (1996) and Paul (2003) both investigate the determinants of demand for individual games in the National Hockey League, while Borland and Lye (1992) conduct a similar analysis for Australian Rules football. Brown, Spiro and Keenan (1991), and Burdekin and Idson (1991) estimate attendance functions for professional basketball.…”
Section: Literature Reviewmentioning
confidence: 99%